Young People's Perceptions of Transitioning from School to Higher Education: A Cross-National Perspective - Rojon, Céline; Hernandez, Javier; Knauer, Mira; Mocca, Elisabetta (International Journal of Educational and Life Transitions, 2023)
Education can provide individuals access to work and career possibilities. It may also contribute to greater societal equality, facilitating social mobility. The transition from secondary school (SEC) to higher education (HE) (and beyond) is particularly important, impacting both on individuals’ lives and on society more widely (e.g., by supplying labor markets with required qualifications). Taking an interdisciplinary, cross-national perspective, we conducted semi-structured interviews with 23 young people from Germany, Argentina, and Chile, aiming to enhance understanding of individuals’ perceptions of barriers and facilitators of transitioning from SEC to HE, in the context of their personal/family situations, social structures and cultural environments. Thematic data analysis pointed to commonality in terms of what young people from the three countries consider as facilitators (e.g., personal ambition; support from family/friends) and barriers (e.g., high expectations of oneself/family/friends; lack of interest in study subject). Unsurprisingly, given the three countries’ distinct educational systems, societal structures, cultural values etc., the findings also revealed some differences across the three cases, such as role models acting as an important facilitator much more in Germany compared to Chile and Argentina. We conclude that many contextual and personal factors can both facilitate and hinder young people from accessing to and thriving in HE, most of which are relevant to individuals regardless of their country of origin. Further research could expand our qualitative study, for instance, through a large-scale, quantitative study across a wider range of countries.
Keywords: transition; school-to-higher education; subjectivity; interviews; facilitators; barriers